EIJI TAKAHASHI: Kaisha-hō no keiju to shūren [Reception and Convergence of Corporate Law] - Naka, Takuma (Zeitschrift für Japanisches Recht, 2016)
Yūhikaku, Tōkyō 2016, XIII + 430 p., 8,500 ¥ ; ISBN: 978 4 64 113739 4